The first species of Cantharis from Ukrainian Rovno amber (Coleoptera, Cantharidae) - Fanti, Fabrizio; Pankowski, Maximilian G. (Zootaxa, 2023)
Cantharis michaeli sp. nov. is described and illustrated from Upper Eocene Rovno amber from Ukraine. This is the first fossil Cantharis (soldier beetles, Cantharidae) from this deposit. The new species is compared with other fossil species of the genus Cantharis. It is similar to C. raeorum Fanti & M. G. Pankowski, 2020, but C. michaeli sp. nov. has a larger body, shorter antennae, and slight differences in both its antennae and pronotum. A review is provided of other soldier beetles found in Rovno amber, as well as a brief overview of the paleoenvironment where this amber formed—an area that included extensive forests, large rivers, and warm temperatures.